Training physiotherapy students to educate patients: A randomised controlled trial. Issue 2 (February 2018) - Forbes, R.; Mandrusiak, A.; Smith, M.; Russell, T.
Highlights: Patient education training enhances self-efficacy of physiotherapy students. Physiotherapy student patient education skills are enhanced following training. Patient education training can be successfully embedded into existing physiotherapy programs. Abstract: Objective: To determine the effect of a training intervention on physiotherapy students' self-efficacy and skills in the area of patient education. Methods: Final year physiotherapy students were randomised to an intervention group or a wait-list control group. The intervention group participated in a 3.5 h training intervention about patient education that included video observation, simulated patient practice and structured feedback. The control group did not receive any training. Self-efficacy was assessed at baseline (T1) and after the intervention (or no intervention for the control group) (T2). Patient education performance was assessed by a blinded rater from a video-recorded standardised clinical examination. Results: 83 students were randomised to the intervention group and 81 students to the control group. There were no differences in demographic variables or self-efficacy between groups at baseline. There was significant improvement in self-efficacy for the intervention group, but no change for the control group. The intervention group performed significantly better than the control group for nine of the eleven performance items, with significantly higher scores overall. Conclusion: A training intervention enhances physiotherapy student self-efficacy and performance in patient education. Practice implication: Use of patient education training is recommended to enhance student self-efficacy and performance.